Hydrodynamic effect of hand flow on kicking in front crawl swimming - Ichikawa, H.; Shimojo, H.; Yamashiro, S.; Shimoyama, Y. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Swimming is an interaction between the swimmer and the water. Swimmers produce propulsive force using upper and lower limbs. In most swimming styles the current created by the upper limbs can be regarded as upstream and the current created by the lower limbs as downstream. Flow created upstream by the upper limb could affect the flow created by the lower limb located downstream. The purpose of the study was to investigate the effect of the flow created by the upper limb on kicking during front crawl swimming. METHODS A competitive swimmer participated in the study. The trials consisted of 25m front crawl and flutter kicking swimming with maximal effort. Four pressure sensors (PS-05KC, Kyowa Electronic Instruments Co. Ltd., Japan) were attached on the swimmer`s right foot to estimate the fluid force produced by the swimmer`s kicking. In addition, the particle image velocimetry (PIV) method was used to visualize the flow from hand to foot in front crawl swimming. RESULTS It was not observed any obvious effect of the hand flow on the estimated fluid force of the kicks in front crawl swimming. Hand flow was visualized during stroke motion, but most of the flows disappeared before reaching the kicking area. Only a few trials showed the hand flow reaching the swimmer`s foot. DISCUSSION While the interaction of the flows from the upper and lower limbs should be discussed carefully, it was suggested that the effect of the hand flow on the fluid force of the kick would be small. This is because the fluid force estimated from the measurement of pressures was not observed to be changed by the hand flow. Although flow from the upper limb to the lower limb was observed in a few trials, most of the hand flow would disappear before reaching the swimmer's foot.